Prenatal Diagnosis and Management of Tuberous Sclerosis Complex with Cardiac Rhabdomyoma: A Case Report Highlighting the Role of Sirolimus and Postnatal Complications - David Asael Rodríguez-Torres; Joel Arenas-Estala; Ramón Gerardo Sánchez-Cortés; Iván Vladimir Dávila-Escamilla; Adriana Nieto-Sanjuanero; Graciela Arelí López-Uriarte (Diagnostics)
Background and Clinical Significance: Tuberous sclerosis complex (TSC) is an autosomal dominant disorder caused by pathogenic variants in TSC1 or TSC2. Cardiac rhabdomyoma is a common prenatal finding and can be associated with severe complications, including pericardial effusion. We administered prenatal sirolimus to mitigate pericardial effusion, which led to postnatal complications. Case Presentation: A 28-year-old pregnant woman with no significant family history underwent routine fetal ultrasound at 28.1 weeks of gestation, which identified a large right ventricular mass consistent with rhabdomyoma. Further fetal brain MRI revealed cortical-subcortical tubers and subependymal nodules, leading to a clinical diagnosis of TSC. At 30.4 weeks, oral sirolimus (3 mg/day) was started due to the significant pericardial effusion. The effusion remained after treatment, requiring pericardiocentesis at 33.6 weeks. The sirolimus dosage was raised to 6 mg/day at 35.6 weeks, reaching a plasma level of 3.76 ng/mL, but there was no discernible improvement because of the continued fluid accumulation. The mother did not experience any adverse side effects from the procedure. Genetic testing confirmed a pathogenic variant in TSC2 (c.1372C>T). After birth, the neonate received a single dose of sirolimus but subsequently developed necrotizing enterocolitis (NEC), highlighting the potential adverse effects and the need for cautious consideration of treatment options. Conclusions: This case illustrates the complexities of managing prenatal tuberous sclerosis complex (TSC). While sirolimus has been explored for fetal cardiac rhabdomyoma and associated complications, its effectiveness in resolving pericardial effusion remains uncertain. Additionally, the development of NEC postnatally raises concerns about the safety of mTOR inhibitors in this context. Further studies are necessary to assess the risks and benefits of this approach in fetal therapy.